2008
DOI: 10.1007/s10903-007-9114-2
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Practices, Drug Use Behaviors, and Prevalence of HIV, Syphilis, Hepatitis B and C, and HTLV-1/2 in Immigrant and Non-immigrant Female Sex Workers in Argentina

Abstract: Effective HIV/STI prevention and medical care programs need to be tailored to the specific needs of both FSW groups in Argentina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 12 publications
2
17
3
1
Order By: Relevance
“…Three studies included intracontinental migrants who had migrated from low-income countries to other low-income countries: Benin,25 Kenya27 and Mali 45. Three studies recruited intracontinental migrants moving from low-income to middle-income countries (Bolivia, Ecuador, Argentina, Uruguay46 47 and Mexico 48…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three studies included intracontinental migrants who had migrated from low-income countries to other low-income countries: Benin,25 Kenya27 and Mali 45. Three studies recruited intracontinental migrants moving from low-income to middle-income countries (Bolivia, Ecuador, Argentina, Uruguay46 47 and Mexico 48…”
Section: Resultsmentioning
confidence: 99%
“…Some studies specified eligibility criteria to include women who self-identified as FSWs23 32 38 or used a standardised Joint United Nations Programme on HIV/AIDS definition 46 47 49 50. Three studies relied on the staff of STI clinics,44 bar managers, health service providers48 or other FSWs to identify participants 26.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,17 Analysis of factors associated with or predicting HIV infection among FSWs and clients has predominantly focused on the individual level, identifying inconsistent condom use, alcohol or other substance use, STI, and number of sexual partners/clients as key correlates of HIV infection. 12,[18][19][20] More recently, however, emerging research has demonstrated the impact of structural factors, such as criminalizing policies, workplace environment, violence, and stigma, on the HIV epidemic among FSWs. 1 In settings where stigma or laws criminalizing sex work or aspects of sex work exist, sex workers may be forced to have sex in locations where safety may be compromised, condom use during sex work may be forfeited or rushed to avoid attracting police attention, or condom distribution by HIV prevention programs may be compromised.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research has shown that immigrant sex workers were more likely to work in entertainment establishments such as bars and cabarets rather than from the streets because of their preference for an environment with more anonymity and less exposure to immigrant officials. 6,7 Asian countries have recently witnessed a major shift in sex work from traditional brothel settings to entertainment establishments such as bars, clubs, and hotels. 3 Sex workers in brothels in most Asian countries [8][9][10][11] have good access to condoms and STI/HIV screening and treatment services due to national 100 % condom use policies targeting these establishments.…”
Section: Introductionmentioning
confidence: 99%